Unpacking boredom factors of Chinese foreign language major students in translation classes: A sequential mixed methods study - Zhang, Tingyu (Frontiers in Psychology, 2022)
Though largely ignored by educators and researchers, boredom, an aversive emotion, is the hurdle for many translation learners to be professional. It is all the more important to unpack the boredom factors of Chinese foreign language major students in translation classes, which will serve in promoting students’ engagement in L2 classes and translator cultivation. By using a sequential mixed approach, this study conducted a thematic analysis and built a structural equation model. Quantitative data were gleaned from 483 foreign major college students in China and qualitative data were selected from students (N=15) of 7 universities through snowball sampling. Initially, the first-order confirmatory factor analysis (CFA) verified the adapted questionnaire and the second-order CFA finds each factor’s contribution. Then, the thematic analysis gives support to the empirical findings. Both quantitative and qualitative analyses revealed that task-based boredom is the most routinely experienced boredom. Moreover, two major sources of boredom in translation classes are found, including task-based boredom and teacher-related boredom. It is suggested that teachers should improve their classes and use more interesting and engaging materials and tasks with the proper level of difficulty. The finding can help educators to identify the major boredom in the translation class and help potential professional translators to grow. Future studies will also be facilitated by the present study to find approaches to tackle these boredom sources.